Hazardous geological processes at incomplete construction sites - A. L. Suzdaleva; M. Yu. Slesarev; I. Yu. Yakovleva (Vestnik MGSU)
Introduction. The purpose of the research is to study the regularities of development of hazardous geological processes caused by the termination of construction of buildings for a long time. These processes include any changes in the Earth’s crust that can have a negative impact on the living conditions of the population and cause economic damage.Materials and methods. The research was carried out on the territory of Moscow, as well as Moscow and Kaluga regions. The subject of the study was the natural and technical system formed in the process of destruction of incomplete construction objects. Special attention was paid to the territories surrounding the long-term abandoned buildings, where no work had been carried out for many years.Results. On the territories surrounding the abandoned incomplete objects, the greatest danger are: suffosion, karst, erosion, landslides, liquefaction of soils and rocks, causing a decrease in their strength. The generalized analysis of the obtained data made it possible to create a classification of incomplete construction objects. It simultaneously takes into account the condition of building structures and hazardous changes in the surrounding area. The practical application of the classification will provide a systemic character of activities aimed at solving the problem of abandoned buildings. Assigning a certain status to an unfinished construction object can serve as a justification for its restoration or liquidation. A programme for depreservation of incomplete objects was developed.Conclusions. An adequate idea of the impact of an unfinished construction project on living conditions in the city can only be given by studying the natural and technical system that formed during the period of stoppage of work. Its main elements are: an incomplete building and a site where the development of hazardous processes caused by destruction is observed. It is necessary to create an information array on incomplete construction objects, which would include long-term abandoned buildings that are not subject to restoration. The depreservation of incomplete buildings for their further construction should be carried out after a mandatory study of tendencies in the development of dangerous geological processes that occurred during the period of construction stoppage.